Shear properties and dynamic responses of greases in a micrometer-order gap - Chun, Hanul; Hirayama, Tomoko; Yamashita, Naoki; Hatano, Naoya; Tatsumi, Kazuya; Kuriyama, Reiko (Frontiers in Mechanical Engineering, 2024)
Grease is used as a lubricant in a wide range of fields, including bearings, because it reduces friction and prevents harmful wear of components, protecting against rust and corrosion and acting as a seal to prevent invasion of dirt and water. While most of the research of grease has focused on the environment inside the bearing, there has been little research on the fundamental lubrication mechanism of grease. It is known that thickeners, which keep a complex three-dimensional structure in the grease, have a significant effect on the shear characteristics of grease, and it is assumed that this is due to the orientation of the thickener structure in the shear direction. In this study, the apparent viscosity of grease in a micro-order gap was measured using our original viscometer and it was compared with the apparent viscosity which was measured with a submillimeter order gap rheometer because grease may show different rheological properties against a conventional one. Also, the dynamic response of viscous resistance that appeared when each grease was subjected to a change in shear force was quantitatively evaluated using relaxation time. As a result, the apparent viscosity remarkably decreased in a micro-order gap compared to a submillimeter one, and two types of shear thinning mechanisms were proposed based on the orientation of the thickener: caused by narrow gap and shear force. Also, the behavior of viscous resistance due to changes in shear force depended on the type of thickener. It was also confirmed that the relaxation time of each grease correlates with its oil film-forming ability and the entanglement level of the thickener's structure. Furthermore, the mechanism of the dynamic response was proposed based on the reorientation of thickeners.